THE ROLE OF THE PUBLIC ACCOUNTANT IN CONTRACT TERMINATION. - Queenan, J. W. (The Accounting Review, 1945)
Abstract The article presents information on the role of the public accountant in contract termination. The settlement of terminated contracts involves many problems other than accounting, such as the physical handling and disposal of inventories and equipment. However, there can be no lack of emphasis on the accounting phases of such settlements. The Contract Settlement Act of 1944 has as its purpose the standardization and so far as possible, the simplification of procedures in arriving at such settlements. Although the Act provides for settlement by agreement or negotiation, a careful reading will indicate that accounting is generally considered essential to such settlements. The basis of a settlement by agreement is the contractor's proposal for settlement, which must be prepared and submitted to the proper governmental agency. It should be apparent that such proposal must be based upon a reasonable accounting foundation in order to negotiate a settlement an any basis other than a purely arbitrary one. Provisions of the Contract Settlement Act of 1944, imposing severe penalties in case of fraud or misrepresentation in the settlement proposal, make reliable accounting data equally important for the contractor's own protection.